Fuel Options for Bangladesh-2017 (Journal of Chemical Engineering, 2017)
Fuel is an essential commody supporting our daily life and economy. Until today, the majority of Bangladesh fuel is met from domestic natural gas production. With economy growing (like GDP 7+ %) in coming years, fuel use is also increasing and the local gas prodcution could not meet the requirement. Goverment has already taken steps for the import of LNG and LPG to support the shortfall. This paper describes different fuel options and suggests that the additional fuel requirement might be met with the imported LNG considering the environmental and cost of fuel. LPG is costly than imported LNG. So, emphasis on LPG use may be considered only to the areas where there is no pipe gas supply.Journal of Chemical Engineering, Vol. 30, No. 1, 2017: 27-31